Hak mogok di Indonesia - Uwiyono, Aloysius, 1952- ([Depok] : Universitas Indonesia, Fakultas Hukum, Program Pascasarjana, 2001)
Legal aspects of strikes and labor disputes in Indonesia.
Originally presented as the author's thesis (doctoral--Universitas Indonesia, 2001) under title: Pemogokan di Indonesia dan penyelesaiannya.
Includes bibliographical references (p. 297-313) and index.
Keywords: Strikes and lockouts -- Law and legislation -- Indonesia; Labor disputes -- Indonesia